2007
DOI: 10.1007/s10933-006-9081-y
|View full text |Cite
|
Sign up to set email alerts
|

Holocene development and anthropogenic disturbance of a shallow lake system in Central Ireland recorded by diatoms

Abstract: Three cores from two connected lakes in Central Ireland (Lough Kinale and Derragh Lough) were investigated using diatom analysis to establish the Holocene development of the lacustrine system, any local variations within the lakes and any anthropogenic influences. The study area was situated in a lowland location and the lakes were shallow, unstratified and interconnected. Litho-and bio-stratigraphical analyses of the lake cores and deposits beneath a mire separating the two lakes showed the changing spatial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…6 ), indicating lake shallowing. Given that the lake outlet is on bedrock, this apparent ‘lake-shallowing’ can only be caused by the creation of a ‘shore-edge’ as the crannog is constructed 17 . Values of Ti, taken as an indicator for in-wash of mineral particles, show an increase, compared to background values, at the start of the crannog phase, concomitant with changes in other proxies.…”
Section: Resultsmentioning
confidence: 99%
“…6 ), indicating lake shallowing. Given that the lake outlet is on bedrock, this apparent ‘lake-shallowing’ can only be caused by the creation of a ‘shore-edge’ as the crannog is constructed 17 . Values of Ti, taken as an indicator for in-wash of mineral particles, show an increase, compared to background values, at the start of the crannog phase, concomitant with changes in other proxies.…”
Section: Resultsmentioning
confidence: 99%
“…4) were observed. Moreover, there is an increase in tychoplanktonic and periphytic diatom taxa, such as "Fragilaria" taxa like Ulnaria acus, that could suggest inwash of diatom species from other habitats (Selby and Brown, 2007) with the development of aquatic plants in the littoral zone or more turbid conditions (Selby and Brown, 2007;Baier et al, 2004). Miras et al (2015) confirmed the presence of aquatic plants by observing that algae (Pediastrum, Spirogyra) progress, parallel to a rise in the presence of rotifer resting eggs.…”
Section: Palaeoecological Reconstruction For the Lake And Landscape S...mentioning
confidence: 95%
“…6dB) and, 2) the development of hemp cultivation and retting with an increase in detrital material into the lake (presence of NPPs associated to soil disturbance as Diporotheca rhizophila) (Miras et al, 2015). The different uses exercised by man on the catchment could explain the increase in tychoplanktonic "Fragilaria" diatoms that could be linked with possible inwash of surrounding soil-derived material (Baier et al, 2004;Selby and Brown, 2007). This increase could also be linked to the hemp cultivation.…”
Section: Palaeoecological Reconstruction For the Lake And Landscape S...mentioning
confidence: 99%